Assessment of the Enablers and Strategies that Promote Effective Integration of Digital Technologies (DTS) for Sustainable Housing Practices in UK. (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This research work investigates the enablers and strategies that promote effective integration of digital technologies (DTs) for sustainable housing in the UK. It engages qualitative research techniques in investigating the application of DTs for promoting sustainable housing practices inthe UK, with a view to highlighting the key DTs driving sustainable housing initiatives in UK. The study adopted Thematic Analysis assumptions in its data analysis. The method of data collection were through semi-structured interviews as primary sources. Other information were drawn from extensive literature reviews of journals, textbooks, printed publications, internet sources and write-ups relevant to the study, from secondary sources. The result from the data analysis shows that there are various DTs that aid sustainable housing practices. To acknowledge the roles these DTs play in promoting sustainable housing practices in the building industry, the knowledge of their application and in-depth understanding on their use is critical. The researcher concluded that the integration of digital technologies (DTs) for promoting sustainable housing practices in the UK hinges on identifying and leveraging key enablers such as robust policy frameworks, industry collaboration, and ongoing innovation in technology. Effective strategies encompass the adoption of smart building systems, the use of data analytics for optimizing resource efficiency, and fostering a culture of sustainability through education and stakeholder engagement. These elements collectively drive the transition towards more sustainable housing, ensuring long-term environmental and economic benefits. One of the recommendations was that focus should be made on developing comprehensive training programs for stakeholders, including architects, builders, and policymakers, to ensure they are well-versed in digital technologies (DTs) and their applications in sustainable housing. This will facilitate better integration and utilization of these technologies.